DYNAMICS OF A SPACE TETHER IN BINARY ASTEROIDS - Ferreira, A. F. S.; Prado, A. F. B. A.; Guerman, A. D.; Santos, D. P. S. [UNESP]; Burov, A.; Winter, O. C. [UNESP]; Parker, J. S.; Seago, J. H.; Strange, N. J.; Scheeres, D. J. (Univelt Inc, 2018)
The present paper studies the dynamics of space elevators constructed in double asteroids of the solar system, assuming an irregular shape for both bodies. To make this task, a tether is attached to the surface of one of the asteroids, with a spacecraft attached in the other end. The analysis of the equilibrium points to place the tether and the stability of those solutions are made. The irregularities of the bodies, assumed to be ellipsoids, are described by the coefficients of a spherical harmonic expansion. The coefficients of this expansion are functions of the dimensions of the bodies. The equilibrium conditions are studied by searching for the situations where the forces acting in the spacecraft have a zero resultant, assuming that only the gravity of both irregular bodies are present in the system. The method is applied in the double asteroid systems (3169) Ostro and (90) Antiope, which are synchronous systems. To verify the effects of the irregularities of the bodies in the solutions, calculations are also made assuming that the bodies are spherical.